Causes and Effects of Drug Abuse in District Karak, and Their Solutions in the Light of Islamic Teachings - Mr. Muhammad Adnan; Mr. Bilal Hussain; Mr. Mubashir Hassan (Journal of Religion and Society, 2025)
Drug abuse is a destructive social evil that devastates individuals, weakens families, and erodes the fabric of society. In Pakistan, particularly in Khyber Pakhtunkhwa and its districts, the spread of drugs has become a serious moral and social issue. District Karak, known for its strong tribal values and traditional social structure, has also been affected. Here, many young people and individuals from different walks of life have fallen into addiction, leading to physical, mental, and spiritual harm. Several factors contribute to the spread of drug use, including economic hardship, unemployment, ignorance, negative environmental influences, peer pressure, weak enforcement by government institutions, and lack of proper social supervision. These factors not only destroy an individual’s personality but also damage family life and push society toward moral decline. Islamic teachings strictly forbid all forms of intoxicants, describing them as the "mother of all evils." The Holy Quran and Hadith emphasize their prohibition. The Prophet Muhammad (peace be upon him) declared addiction to be contrary to both faith and reason and instructed Muslims to completely avoid it. Therefore, it is necessary to adopt Islamic principles to eliminate drug abuse, take firm action at the government level, raise public awareness, and strengthen family and social monitoring to protect society from this scourge. This research highlights the causes and effects of drug abuse in District Karak and suggests effective solutions based on Islamic teachings. By implementing these measures, society can be safeguarded from the devastating impact of this menace. Key Words: Causes , Effects , Spread of Drugs , District Karak ,Islamic Teachings.